Motherhood online: Issues and opportunities for discourse analysis. (April 2021) - Mackenzie, Jai; Zhao, Sumin
Abstract: This article collection is a response to the rapid acceleration of research interest in 'motherhood online', defined here as a field concerned with the production and reception of digital media that is produced by mothers and/or about motherhood, and is related to issues of maternal identities, communities or practices. It contributes to this field of study by presenting a selection of six articles that examine these concerns from a discourse analytical perspective. These articles explore a range of socio-maternal practices such as experiential knowledge-sharing (Lyons) and infant feeding (Coffey-Glover), and experiences such as maternal regret (Matley) and postnatal depression (Kinloch & Jaworska). They examine contemporary concepts of motherhood and mothering practice as they intersect with domains such as religion (Ringrow), healthcare (Coffey-Glover; Kinloch & Jaworska) and gendered (in)equalities (Lazar & Ke). Further, the articles consider the opportunities and challenges that arise when individuals navigate these issues in a range of online contexts, from now well-established sites such as blogs (Coffey-Glover; Ringrow) and online forums (Kinloch & Jaworska; Matley), to newer forms of digital media including messaging apps (Lyons) and video-sharing platforms (Lazar & Ke). In this introduction, we summarise some key themes of motherhood online research to date, outline the rationale for a discourse analytical perspective in this field, and locate this article collection within a broader interdisciplinary context.